Spanduk Penolakan Vaksin Covid-19: Kajian Semiotik Multimodal - Arini Prishandani; Nurainun Ainun; T. Thyrhaya Zein (Balai Bahasa Sumatera Utara, 2021)
The purpose of this study was to see the meaning of the Covid-19 vaccine rejection advertisement or banner on social media on the @Indonesian_flatearth_society account. The method used in this research was qualitative method. The method to analyze using semiotic analysis of verbal and visual communication by Kress van Leeuwen. The analytical technique used in this research was reading image. The source of this research data was taken from the Covid-19 vaccine rejection campaign advertisement on Instagram social media